DARSV: a dynamic agent routing simulator for VANETs. (3rd November 2021) - Harrabi, Samira; Jaafar, Ines Ben; Ghedira, Khaled
In this paper, a novel dynamic agent routing simulator for vehicular ad-hoc networks (DARSV) is presented. The main purpose of DARSV simulator is to realise a successful large-scale simulation of agent based routing approach in vehicular networks. To conduct this goal, the proposed simulator combines the Java Agent DEvelopment (JADE) which is a powerful multi-agent system (MAS) framework with the dynamic ad hoc routing simulator (DARS) that takes into account the dynamic nature of environment networks. The simulation results are discussed to evaluate the efficiency and the performance of the proposed simulator.